Lymphocytes in Cellular Therapy: Functional Regulation of CAR T Cells - Dwivedi, Alka; Karulkar, Atharva; Ghosh, Sarbari; Rafiq, Afrin; Purwar, Rahul (Frontiers in Immunology, 2019)
Lymphocytes especially autologous T cells have been used for the treatment of numerous indications including cancers, autoimmune disorders and infectious diseases. Very recently, FDA approved Chimeric Antigen Receptor T cells (CAR T cells) therapy for relapse and refractory CD19+ B cell Acute Lymphocytic Leukaemia (r/r B-ALL) and r/r diffuse large B cell lymphoma (r/r DLBCL) upon their remarkable success in multiple Phase I-II clinical trials. While CAR-T cells are considered as major breakthrough in the field of cancer immunotherapy, the regulation of CAR-T cells remains poorly understood. In this review we will discuss the strategies that regulate the CAR-T cell efficacy and persistence with focus on roles of different structural component of CAR construct on efficacy and toxicity. Different domains of CAR construct, for example, antigen binding domain, hinge, transmembrane and signalling domain as well as immune-regulatory cytokines have significant impact on CAR T cell efficacy. Finally, this review will highlight the strategies that will promote CAR-T cells efficacy and will reduce the toxicity.